ISLAMIC BUSINESS ETHICS IN (PRODUCTION, DISTRIBUTION AND CONSUMPTION, PERSPECTIVE OF THE QUR'AN AND HADITH) - Fuad; Dudin Shobaruddin; Nur Kholid (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2023)
The Qur'an and Hadith are human guidelines in life, in which all matters such as verses and hadiths related to one's ethics in the production, distribution and consumption of halal products have been regulated. The purpose of this research is to see what the perspectives of the Qur’an and Hadith regarding the ethics of production, distribution and consumption are, and to see opportunities in the halal industries in Indonesia. By using the research methodology of literature review or literature study, with descriptive research. The result of the study shows that (1) there are many verses and hadiths that discuss the ethics in production, distribution, and consumption, at least 16 verses of the Qur'an and 14 hadiths are discussed in the research, (2) the perspective of the Qur'an and hadith in production, distribution and consumption must be halal and tayyiban. For it to be considered Halal, we need to observe from how it is produced, getting the ingredients, buying, and selling it and finally consuming it. (3) And there are seven opportunities for the halal industry in Indonesia that can be developed.